Penyuluhan Hukum Analisis Sosial sebagai Strategi Perubahan Sosial di Masa Penerimaan Anggota Baru (MAPABA) Pergerakan Mahasiswa Islam Indonesia (PMII) Sumatera Selatan - Junaidi Junaidi; Mila Surahmi; Desmawaty Romli (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This community service aims to provide education and guidance to new members of the Indonesian Islamic Student Movement (PMII) South Sumatra, especially students, in analyzing and providing solutions to social problems around their environment. The method used in this service was counseling, followed by a discussion. The instrument of the activity was a questionnaire, and the data analysis technique used descriptive analysis. The results of this community service activity provided an understanding for students who are members of the Indonesian Islamic Student Movement (PMII) to apply their social analysis more sensitively and empathetic. It can support a sense of brotherhood between members and the community, increasing a sense of security, peace, tranquility, and prosperity.